The encyclopedia of sexually transmitted diseases - Shoquist, Jennifer; Stafford, Diane (Facts on File library of health and living, 2004)
Presents approximately one thousand alphabetized entries on sexually transmitted diseases, covering the various types, preventive methods and treatments, laws and foundations, and other topics related to these illnesses, and includes an extensive bibliography and other references and resources